Penurunan Gejala Baby Blues Melalui Terapi Musik Klasik Mozart Pada Ibu Post Partum - Fitri Nuriya Santi; Siti Noviana Wahid (Jurnal Kesehatan Panca Bhakti Lampung, 2019)
The birth of a baby confirms a new status for a woman, which is to be a mother. The existence of this new status requires mothers to make various adjustments that can cause stress both physically and psychologically. Baby blues are psychological problems that often occur in postpartum mothers. The symptoms of these baby blues result in feelings of discomfort for the mother and can progress to more severe psychological disorders. It needs good treatment to reduce the symptoms of baby blues in postpartum mothers. The aim of this research is to find out and analyze the effectiveness of mozart classical music therapy to reduce the symptoms of baby blues in Post partum mothers. The method used in this study is to provide a description of a problem. The instrument for assessing baby blues symptoms in this study used the Edinburgh Postnatal Depression Scale (EPDS). The results of this study indicate that after being given the application of mozart classical music therapy in both respondents there was a decrease in the symptoms of baby blues. The conclusion of this study is that the application of mozart classical music therapy in both respondents was effective in reducing the symptoms of baby blues. This research is expected to increase the knowledge of the nursing profession in implementing classical mozart music therapy interventions to reduce the symptoms of baby blues in postpartum mothers.